What's the party like? the status of the political party in anti-defection jurisdictions - Bhatia, U (Springer, 2021)
This paper explores how political parties should be regulated in jurisdictions with anti-defection laws, which constitutionalise parties’ control over the legislative process. It begins by arguing that parties in such jurisdictions should be understood as neither private organisations nor quasi-public bodies but as legislative entities. Next, it argues that recognising the legislative status of the party should affect how we think about the legal regulation of its internal affairs. In particular, the law may justifiably demand that decision-making power within the extra-parliamentary party be dispersed across multiple persons and not concentrated in the hands of a few. Finally, I examine the implications of this argument for India and Pakistan, two jurisdictions with anti-defection laws in place.